Revisiting the Environment Effect on Mass Transfer for Heterogenized Pd6Ru8 Metal‐Organic Cage Photocatalyst Confined within 3D Matrix. Issue 39 (30th May 2022) - Wu, Dong‐Jun; Luo, Yucheng; Li, Xuan; Su, Zhi‐Fang; Shi, Jian‐Ying; Su, Cheng‐Yong
Abstract: Artificial light‐driven splitting of water into hydrogen involves multiple links to emulate natural photosynthesis, including light absorption, electron or energy transfer, surface catalysis et al., in which, the mass transportation of sacrificial reagent and reactant is always ignored. Metal‐organic cage (MOC) of Pd6 Ru8 (MOC‐16), assembling multiple photosensitive Ru and catalytic Pd concomitant with directional electron transfer between them, provides an opportunity to explore the environmental effects from the view point of mass transportation without disturbance of other links. Zr‐MOF of UiO‐66 is used as a matrix to heterogenize MOC‐16 and a series of characterizations are carried out to unravel the composition, structure and optical properties. The intact MOC‐16 remains with long‐term photo‐stability and the outstanding photocatalytic activity is obtained by virtue of a long‐lived triplet state. Three matrixes of ZIF‐8, ZIF‐8 derived carbonate CZIF, and UiO‐66 are intercompared for mass transfer based on wettability and porous structure. Water molecule directly takes part in the formation of H2 catalyzed by MOC‐16@UiO‐66, evidenced by a kinetic isotope effect, in addition to the proton delivery thanks to the hydrophilic nature of UiO‐66. The porous structure of UiO‐66 is essential for the permeation of sacrificial reagent to serve as two‐electron donor, in sharp contrast as one‐electron donor in nonporous CZIF matrix. These results highlight the importance of microenviroment surrounding molecular catalysts in view of the heterogenization of molecular catalysts, meanwhile, providing a prominent guidance on how to choose 3D support to bridge the homogenous and heterogenous system. Abstract : Water directly takes part in the formation of H2 catalyzed by MOC‐16@UiO‐66, evidenced by a kinetic isotope effect, in addition to the proton delivery thanks to the hydrophilic nature of UiO‐66. The porous structure of UiO‐66 is essential for the permeation of sacrificial reagent to serve as two‐electron donor, in sharp contrast as one‐electron donor in nonporous CZIF matrix.